Epidural analgesia during labour: its influences on pain relief, progress of labour, mode of delivery, maternal and foetal - Suneetha, M.; Saritha, A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Today, the availability of regional anaesthesia for labour is considered a reflection of standard obstetric care. This study is to be conducted in a tertiary care centre with all facilities available for proposed end of proving that epidural analgesia is a safe and effective method for both parturient and the foetus in abolishing pain during labour. Methods: A total of 60 parturients were studied. they were randomly divided into two groups Group 1 includes 30 parturients. In this group parturient received epidural analgesia. The loading dose consisted of 10 ml of Bupivacaine 0.1% and Fentanyl 0.0002% (20 mcg). The top up doses were 10 ml of 0.1% Bupivacaine and Fentanyl 0.0002%, administered whenever the parturient complained of pain. When parturients enters into second stage a further 12-15 ml was injected with parturient in sitting position or semi-sitting position. Group 2 - (control group) Includes 30 parturients. In this group parturient was monitored without any analgesia. Results: This prospective study was done to assess the effect of epidural analgesia on the progress of labour and its outcome, to evaluate its efficacy as an analgesic technique and to study the maternal and fetal outcome. The total number of 60 parturients were selected and randomly categorized into two groups. CASE-Those who received epidural analgesia, CONTROL-Those who did not receive any analgesia. Conclusions: Epidural analgesia provides a versatile method of administering effective and satisfactory pain relief to parturient women. The technique should not be considered as a single entity, because the type and the dose of epidural medication can be altered as needed.